Effectiveness of Social Media Message Framing on Caries Risk Perception among Health Science Students: A Quasi-Experimental Study Based on the Health Belief Model - Idamawati Nababan; Member Reni Purba; Niki Yuchinda (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Despite increasing access to oral health education, the prevalence of dental caries remains high among health science students, indicating a gap between theoretical knowledge and individual risk perception. This study aimed to evaluate the effectiveness of message framing strategies delivered via social media in enhancing caries risk perception, based on the Health Belief Model (HBM). This study employed a pretest-posttest quasi-experimental design with a control group. A total of 130 students from the Faculty of Dentistry at Prima Indonesia University were selected using purposive sampling and divided into an intervention group (n = 65) and a control group (n = 65). The intervention group was exposed to gain-framed and loss-framed health messages through social media over one month, while the control group received no intervention. Risk perception was measured using six core HBM constructs and analyzed using the Wilcoxon Signed-Rank Test and Mann–Whitney U Test. The results showed statistically significant improvements (p< 0.001) in perceived susceptibility, severity, benefits, cues to action, and self- efficacy in the intervention group, while perceived barriers showed no significant change. These findings suggest that social media–based message framing is effective in improving caries risk perception and may help bridge the gap between knowledge and behavior among the productive-age population Keywords: Dental Caries, Digital Health Promotion, Health Belief Model, Message Framing, Risk Perception, Social Media Intervention